The Poetics and Politics of Alzheimer's Disease Life-Writing - Martina Zimmermann (Palgrave Studies in Literature, Science and Medicine, 2017)
This is the first book-length exploration of the thoughts and experiences expressed by dementia patients in published narratives over the last thirty years. It contrasts third-person caregiver and first-person patient accounts from different languages and a range of media, focusing on the poetical and political questions these narratives raise: what images do narrators appropriate; what narrative plot do they adapt; and how do they draw on established strategies of life-writing. It also analyses how these accounts engage with the culturally dominant Alzheimer's narrative that centres on dependence and vulnerability, and addresses how they relate to discourses of gender and aging. Linking literary scholarship to the medico-scientific understanding of dementia as a neurodegenerative condition, this book argues that, first, patients' articulations must be made central to dementia discourse; and second, committed alleviation of caregiver burden through social support systems and altered healthcare policies requires significantly altered views about aging, dementia, and Alzheimer's patients.